A preclinical study on the influence of linkers in [68Ga]Ga-NOTA-X-RM26 radiotracers for PET imaging of GRPR expression - Esther Olaniran Håkansson; Ivan V. Zelepukin; Karim Obeid; Athanasios Bitzios; Ekaterina Bezverkhniaia; Amulya Sunkara; Ulrika Rosenström; Anna Orlova; Luke R. Odell; Panagiotis Kanellopoulos (EJNMMI Research)
Abstract Background Gastrin-releasing peptide receptor (GRPR) is overexpressed in several cancers, including prostate and breast, making it an attractive target for radiopharmaceutical development. Studies on GRPR-targeting radioligands highlight the critical role of the spacer region between the GRPR-recognition motif and radiolabeled moiety, which can significantly influence peptide pharmacokinetics and pharmacodynamics. Herein, we investigated the impact of structurally restricted spacers on the performance of RM26-based radioligands. Results Three novel radioligands were designed to each bear a NOTA chelator via different spacers composed of N-acetyl-lysine followed by either o-ethyltoluene (oET), o-methylanisole (oMA), or m-methylanisole (mMA) motifs. The peptides were successfully labeled with Ga-68, achieving high radiochemical yield, purity, and molar activity. The resulting [68Ga]-labeled peptides demonstrated high and GRPR-specific binding to prostate cancer PC-3 cells, antagonistic behavior, and the IC50 values to GRPR were in the single-digit nanomolar range. Biodistribution studies at 2 h post-injection in PC-3 xenograft-bearing mice revealed high, GRPR-mediated tumor uptake for all three radioligands. In addition, high hepatobiliary excretion with elevated uptake in the liver and the gastrointestinal tract and pronounced pancreatic uptake were observed. Conclusions Among the three radioligands, the peptide bearing the N-acetyl-lysine-oET spacer exhibited the fastest background clearance and better PET imaging of prostate cancer xenografts. The incorporation of conformationally restricted spacers is a promising strategy for developing tracers with high GRPR binding and good imaging properties, but further optimization is necessary to reduce uptake in healthy tissues.